Change in psoriatic arthritis outcome measures impacts SF-36 physical and mental component scores differently: an observational cohort study. Issue 3 (2nd November 2021) - Skougaard, Marie; Jørgensen, Tanja S; Jensen, Mia J; Ballegaard, Christine; Guldberg-Møller, Jørgen; Egeberg, Alexander; Christensen, Robin; Benzin, Peter; Stisen, Zara R; Merola, Joseph F; Coates, Laura C; Strand, Vibeke; et al.
Abstract: Objective: The objective was to investigate interplay and physical and mental component scores between change (Δ) in health-related quality of life (HRQoL) quantified by the physical component score (PCS) and mental component score (MCS) retrieved from short-form health survey (SF-36), change in disease activity (ΔDAS28CRP) and manifestations of PsA. Methods: PsA patients initiating new medical therapy were enrolled. Independent disease measures evaluating disease activity, enthesitis, psoriasis, pain and fatigue were collected at treatment initiation and after 4 months. Interplay between independent disease measures and dependent outcome measures, ΔPCS and ΔMCS, was described with univariate regression analyses. Multivariate regression analyses were applied to assess the impact of independent variables, such as individual disease outcome measures vs ΔDAS28CRP on ΔPCS and ΔMCS. Results: One hundred and eight PsA patients were included. In the univariate regression analyses, improvement in fatigue, pain and disability were associated with improvement in ΔPCS (β; −2.08, −0.18 and −13.00, respectively; all P < 0.001) and ΔMCS (β; −1.59, −0.12 and −6.07, respectively; P < 0.001, P < 0.001 and P = 0.003, respectively). When patient-reported outcomes were included in the final multivariate models, improvements in ΔPCS and ΔMCS were associated with improvements in pain, fatigue and disability ( P < 0.001). Improvement in enthesitis impacted ΔPCS positively (β −0.31, P < 0.001). No association was found between change in skin psoriasis, ΔPCS and ΔMCS (β 0.15, P = 0.056 and β 0.05, P = 0.561, respectively). Conclusion: In this PsA patient cohort, diminishing pain, disability and fatigue improved PCS and MCS significantly. Changes in enthesitis and psoriasis did not grossly impact HRQoL compared with DAS28CRP. Individual PsA manifestations influence HRQoL differently, which is important clinically when targeting treatment. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT02572700.